PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE 3 UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI STRUKTUR FUNGSI TUBUH HEWAN DAN TUMBUHAN DI KELAS IV SD - Sonia Fransisca; Nana Hendracipta; Ahmad Syachruroji (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The development of technology is very good for every field area of life. However, the development of technology makes education needed to make new innovations to follow the current development. One of the challenges for education is to fuse every technology into an attractive medium for learning. Therefore, the purpose of the research in this article is toproduce learning media that innovate following technological developments. The research was conducted using Research and Development method. The methods used were analysis, design, development, implementation, and evaluation (ADDIE). After implementing interactive learning and producing learning multimedia based on an articulate storyline 3. After implementing the evaluation, it was carried out to find out whether the purpose of the research was running or not. The media in the research succeeded in getting the "decent" category and the media helped to improve the students’ learning outcomes by 0.81%, which was included in the "high" N-Gain category.